2018
DOI: 10.2131/jts.43.741
|View full text |Cite
|
Sign up to set email alerts
|

The performance of an <i>in vitro</i> skin sensitisation test, IL-8 Luc assay (OECD442E), and the integrated approach with direct peptide reactive assay (DPRA)

Abstract: In all current in vitro skin sensitisation assays, DMSO is used to dissolve water-insoluble chemicals. However, our previous study suggested the superiority of the modified IL-8 Luc assay (mIL-8 Luc), in which X-VIVO TM 15 is used to dissolve chemicals, over the original assay using DMSO (oIL-8 Luc). In this study, to confirm the superiority of the mIL-8 Luc, we first increased the number of chemicals examined and demonstrated the superiority of the mIL-8 Luc, in which the mIL-8 Luc provided 87.6% of sensitivi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…In this study, we first demonstrated that TLR 1, 2, 4, 5, 6, NLR 1 and 2 agonists augmented IL8LA and that LPS dose-dependently stimulated IL8LA with the lowest concentration of 0.03 ng/ml or 0.4 EU/ml. In addition, we have already reported that most of haptens as well as detergents also stimulated IL8LA (Kimura et al, 2015[ 14 ], 2018[ 16 ]). Therefore, IL-8 Luc assay (H) can respond to a variety of environmental contaminants other than endotoxin, such as bacterial toxins from gram positive and negative bacteria and chemical pollutants such as haptens and detergents.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In this study, we first demonstrated that TLR 1, 2, 4, 5, 6, NLR 1 and 2 agonists augmented IL8LA and that LPS dose-dependently stimulated IL8LA with the lowest concentration of 0.03 ng/ml or 0.4 EU/ml. In addition, we have already reported that most of haptens as well as detergents also stimulated IL8LA (Kimura et al, 2015[ 14 ], 2018[ 16 ]). Therefore, IL-8 Luc assay (H) can respond to a variety of environmental contaminants other than endotoxin, such as bacterial toxins from gram positive and negative bacteria and chemical pollutants such as haptens and detergents.…”
Section: Discussionmentioning
confidence: 99%
“…We used THP-G8 cells derived from a human acute monocytic leukemia cell line THP-1 cell line, which contained stable luciferase orange gene (SLO) regulated by IL-8 promoter and stable luciferase red gene (SLR) by G3PDH promoter (Kimura et al, 2015[ 14 ], 2018[ 16 ]; OECD, 2018[ 22 ]; Takahashi et al, 2011[ 28 ]). THP-G8 cells (5x10 4 cells/100 µL/well) in 96-well black plates (Greiner bio-one GmbH, Frickenhausen, Germany) were cultured for 6 hours with lipopolysaccharide (LPS, from E. coli 026:B6 ( > 10,000 EU/mg, Sigma, St. Louis, MO), TLR agonists (InvivoGen, San Diego, CA), NLR agonists (InvivoGen, San Diego, CA), representative haptens, methylisothiazolinone and glutaraldehyde or 10 µL of the collected environmental water autoclaved for 20 min at 121°C and 2 atm.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…THP‐1 is listed in the LL‐100 panel for blood cancer research 3 and is also known as a representative monocyte cell line, which differentiates into macrophages 4 . Focusing on its function as dendritic cells, THP‐1 is employed for the assessment of skin sensitization in the OECD guidelines to test chemicals 5 …”
Section: Introductionmentioning
confidence: 99%